THE STATE OF MEDIA EDUCATION IN THE TEACHING OF NATURAL SCIENCES IN PRIMARY SCHOOL - Ganiyeva Gulkhayo Islam kizi (Galaxy International Interdisciplinary Research Journal, 2021)
The teacher should talk about how he cares about nature protection and careful use of natural resources, introduce students to the laws on nature protection reflected in the Constitution of Uzbekistan, Uzbekistan should be acquainted with the Charter of the nature conservation society. This is very important in the system of spiritual education of young schoolchildren.